Rút gọn chi tiết giúp em với

Question

Rút gọn chi tiết giúp em với
rut-gon-chi-tiet-giup-em-voi

in progress 0
Huy Gia 1 year 2020-10-22T00:08:51+00:00 2 Answers 72 views 0

Answers ( )

    0
    2020-10-22T00:09:58+00:00

    Đáp án:

    Tham khảo 

    Giải thích các bước giải:

     

    rut-gon-chi-tiet-giup-em-voi

    0
    2020-10-22T00:10:15+00:00

    $(1+\frac{x+\sqrt[]{x}}{\sqrt[]{x}+1}).(1-\frac{x-\sqrt[]{x}}{\sqrt[]{x}-1})$

    = $(1+\frac{\sqrt[]{x}(\sqrt[]{x}+1)}{(\sqrt[]{x}+1)}).(1-\frac{\sqrt[]{x}(\sqrt[]{x}-1)}{(\sqrt[]{x}-1)})$

    =$(1+\sqrt[]{x}).(1-\sqrt[]{x})$

    =$1^2-(\sqrt[]{x})^2=1-x$

    CHÚC BẠN HỌC TỐT

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )